Local Wisdom of Bamboo in Traditional Games as an Educational Tool for Elementary School Students at Padepokan Wadya Saung Kasep - Rahma Nur Ainunnasya; Enok Maryani (International Conference on Elementary Education, 2024)
Currently, many elementary school students are not familiar with their local wisdom. This is due to the advancement of technology, which makes the current generation more interested in various modern facilities and tends to overlook traditional aspects. Another contributing factor is the strong influence of globalization, causing cultural and national identity, especially in regional cultures, to shift towards modernization. The purpose of this research is to introduce innovations to elementary school students based on local wisdom as an educational resource. This research uses a qualitative descriptive method. The research subjects were several elementary school students in Bandung City. Some elementary school students participated in an outing class at Padepokan Wadya Saung Kasep and practiced various traditional games available at the Padepokan. Based on the results of this research, it was found that the traditional games at Padepokan Wadya Saung Kasep contain many educational values, and various traditional games there can be utilized as learning media for elementary school levels